Career Planning and Employability: Secondary School Students Perceptions - Haszeri, Nur Ain Natasha; Rodzalan, Shazaitul Azreen (Research in Management of Technology and Business, 2021)
Career planning and employability are the main terms before a graduate steps into the realm of work. Therefore, this study focuses on how secondary school students express their perceptions regarding these two terms. In this study, four issues were identified regarding employability and career planning such as skills mismatch, lack of skills, lack of career guidance, and lack of knowledge about skills, values and interests. The objectives of this study are to examine career planning perceptions among secondary school students, to identify employability perceptions among secondary school students and to determine the relationship between career planning and employability perceptions among secondary school students. Quantitative method is used in this study by distributing the questionnaires to 311 respondents. Demographic analysis, descriptive analysis and correlation analysis were used. Based on the result of data analysis, career planning and employability perceptions stated the high level while there is a positive correlation between career planning and employability perceptions. This study would be significant to secondary school students, teachers, and counsellors as well in order to get better understanding of career planning and employability. For future studies, it is recommended to conduct qualitative research as it helps to understand the perceptions of career planning and employability perceptions among secondary school students.